2015
DOI: 10.1016/bs.apha.2014.11.003
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic Control of Depression-Related Brain States

Abstract: The GABAergic deficit hypothesis of major depressive disorders posits that reduced GABA concentration in brain, impaired function of GABAergic interneurons, altered expression and function of GABAA receptors, and changes in GABAergic transmission dictated by altered chloride homeostasis can contribute to the etiology of Major Depressive Disorder (MDD). Conversely, the hypothesis posits that the efficacy of currently used antidepressants is determined by their ability to enhance GABAergic neurotransmission. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
73
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(77 citation statements)
references
References 323 publications
(399 reference statements)
4
73
0
Order By: Relevance
“…For instance, human and animal studies have demonstrated altered GABA-related inhibitory function in neurodevelopmental disorders, and associated these changes with cognitive deficits in information processing (8, 9). Reduced GABA levels and function may similarly account for disrupted cognitive-emotional processes in MDD (10, 11). For instance, functional neuroimaging identified MDD-related hyperactivity in the default mode network ( DMN ), a set of brain regions including the dorsolateral prefrontal cortex ( dlPFC ), posterior and anterior cingulate cortices ( ACC ), amygdala, and hippocampus (12, 13).…”
Section: Cognitive-emotional Disruption and Excitation-inhibition Balmentioning
confidence: 99%
“…For instance, human and animal studies have demonstrated altered GABA-related inhibitory function in neurodevelopmental disorders, and associated these changes with cognitive deficits in information processing (8, 9). Reduced GABA levels and function may similarly account for disrupted cognitive-emotional processes in MDD (10, 11). For instance, functional neuroimaging identified MDD-related hyperactivity in the default mode network ( DMN ), a set of brain regions including the dorsolateral prefrontal cortex ( dlPFC ), posterior and anterior cingulate cortices ( ACC ), amygdala, and hippocampus (12, 13).…”
Section: Cognitive-emotional Disruption and Excitation-inhibition Balmentioning
confidence: 99%
“…However, accumulating evidence suggests that loss of intra-cortical GABAergic transmission and consequent imbalances in excitatory and/or inhibitory neurotransmission in the PFC contribute to the etiology of stress-related psychiatric disorders (12). C linical studies have reported reduced GABA levels in the frontal cortex of depressed individuals as compared to healthy humans.…”
Section: Pfc Gaba Dysfunction In Stress and Depressionmentioning
confidence: 99%
“…However, multiple labs have contributed to the understanding GABAergic regulation in other brain regions in depression and other related disorders (12, 29). …”
Section: Pfc Gaba Dysfunction In Stress and Depressionmentioning
confidence: 99%
“…Altered levels and signaling of gamma-aminobutyric acid (GABA), the major inhibitory neurotransmitter, is frequently reported in depression [1, 2], anxiety disorder [3], normal ageing [4], and neurodegenerative disorders, including Alzheimer’s disease [5], and in multiple brain regions including the prefrontal cortex [6] and anterior cingulate cortex [7]. Recent studies showed that such reductions of GABA levels in the human brain are associated with cognitive impairments in an age-dependent manner [8] and are further worsened during older age [9].…”
Section: Introductionmentioning
confidence: 99%